(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the interrelationship between language, technology, and society in the modern era of global communication. The rapid development of digital technologies, social media platforms, and artificial intelligence systems has significantly transformed communication processes worldwide. The study analyzes the influence of technological innovations on language development, intercultural communication, and social interaction. Furthermore, the article discusses the positive and negative effects of digital communication on linguistic diversity and cultural identity. The research is based on qualitative and comparative analysis methods.